The challenges of personnel management for public service organizations in the era of technological disruption in Indonesia - Mansyur, Nadhila Adelfrini (Journal of Management and Administration Provision, 2023)
This thesis examines the challenges of personnel management for public service organizations in the era of technological disruption in Indonesia. The advent of new technologies has significantly impacted various aspects of personnel management, including the adoption of technology-enabled HR systems, the redesigning of job roles and responsibilities, and the need for upskilling and reskilling initiatives. The thesis begins with an introduction that highlights the context and significance of the topic, followed by a thorough review of the relevant literature and theoretical frameworks. The methodology section outlines the research approach and data collection methods utilized in the study. The findings of the study reveal that the adoption of technology-enabled HR systems brings both opportunities and challenges. While these systems enhance efficiency and streamline processes, they also require careful consideration of factors such as employee training, data security, and resistance to change. Furthermore, the era of technological disruption necessitates the reevaluation and redesigning of job roles and responsibilities to align with emerging technologies. This requires organizations to proactively identify the impact of technology and develop strategies to equip employees with the skills needed for the digital age. The thesis explores the significance of enhancing employee engagement and motivation in the face of technological disruption. Clear communication, employee recognition, career development opportunities, work-life balance initiatives, empowerment in decision-making, and employee development programs are identified as crucial factors in fostering employee engagement and motivation.